Polycyclic aromatic hydrocarbons in settled dust particles in selected Ghanaian environments: Levels, source characterization, and assessment of inhalational health risks. Issue 1 (February 2016) - Essumang, D. K.; Ofori, J.; Dodoo, D. K.; Adjei, J. K.
Deposited total particulate matter samples were collected from 10 indoor sites within the Cape Coast and Komenda Edina Eguafo Abrem Municipalities of Ghana and analysed for polycyclic aromatic hydrocarbons (PAHs) using a Varian Gas Chromatography/Mass Spectrometry (GC/MS) system with 8400 auto-sampler. Quality control analysis using National Institute of Standards and Technology Standard Reference Material 1941B gave the PAH recoveries of 80.5% or better. The concentrations of the various individual PAHs in the particulate matter ranged from below detection limits to 3240 µg/kg. The results compared well with a similar study carried out in Palermo, Italy, which had concentrations between 0.01 and 25838.0 µg/kg. Assessment of their sources showed the emission of PAHs was from both combustion and petroleum sources. The cancer risk level for the various sites ranged between 2.6 × 10 –7 and 3.6 × 10 –4 with the upper limit being higher than the acceptable level of 10 –5 . The mutagenic risk levels of the PAHs in the air particulate matter collected from various sites also ranged from 2.0 × 10 −6 to 3.3 × 10 −4, showing certain levels of health risks. This study suggests that indoor air pollution, which has been relegated in most developing countries, should be taken seriously.